Sport and tourism : strategies to develop tourist destinations - Valeri, Marco (Emerald Publishing Limited, 2023)
The links between high profile sports events and tourism are increasingly apparent, yet comparatively little attention has been paid to lower profile sports-related travel. Developing this type of travel provides clear economic and social impacts - employment opportunities, investment, development, the foundation of new infrastructure and the improvement and reinforcement of local communities. Sport and Tourism offers a comprehensive analysis of how and why interorganizational cooperation between sports and tourism occurs to develop tourist destinations. Considering new strategies and crisis management programs, the chapter authors cover a range of sports from football and cycling to winter sports and hiking in countries around the world, such as China, Croatia, Greece, India, Italy, Malaysia, Portugal, UK and Slovakia. In confronting growing concerns around environmental, social and economic issues facing sports and tourism, this collection presents different perspectives to develop new plans for future needs and problems. Sport and Tourism provides an opportunity to stimulate academic research on the relationship between sport and tourism with multidisciplinary approaches. Furthermore, this work encourages discussion among international scholars on how to stimulate cooperation strategies on sport and tourism to develop tourist destinations.
Keywords: Sports and tourism.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Tourism industry.; elektronické knihy; electronic books